Mettl3/Eed/Ythdc1 regulatory axis controls endometrial receptivity and function - Xiujuan Hu; Jincheng Li; Chenyue Ding; Jing Jiang; Wenjuan Xia; Jiafeng Lu; Huapeng Su; Ming Zhang; Hong Li; Ji-long Liu; Yuan Lin; Qingxia Meng; et al. (Communications Biology)
Abstract The regulatory mechanism between N6-methyladenosine (m6A) RNA methylation and histone modification in endometrial receptivity remains poorly understood. In this study, we depict that RIF induced m6A and Mettl3 level restrain, affecting H3K27me3 modification and chromatin accessibility. We show that Mettl3 deletion in the endometrium alters mRNA m6A methylation via Eed interaction. This reduces m6A recognized by Ythdc1, which recruits Eed to suppress H3K27me3 modification co-transcriptionally. The reduction of H3K27me3 disrupts chromatin accessibility and impairs transcription of genes critical for endometrial receptivity. Collectively, these results shed light on a Mettl3-Eed-m6A-Ythdc1 axis that links m6A and histone modification in regulating local chromatin state and gene expression, advancing our understanding of the epigenetic crosstalk between RNA and DNA modification in infertility disease.